Double gradient composite dielectric with high energy density and efficiency. Issue 28 (7th July 2022) - Shang, Yanan; Feng, Yu; Zhang, Changhai; Zhang, Tiandong; Lei, Qingquan; Chi, Qingguo
Abstract : By reasonably adjusting two-dimensional filler double gradient distribution, the restrictive relationship between breakdown strength and dielectric constant is balanced, and the synergistic improvement of breakdown and polarization is realized. Abstract : Composites that possess ultrahigh breakdown strength together with a high dielectric constant have always been the pursuit of energy storage polymer-based dielectrics. However, the constrained relationship between them makes the uniformly filled composite dielectric to usually tend to improve the performance of one at the cost of the other, resulting in a serious restriction on the improvement of the energy storage performance. In this paper, the optimized blend is used as a polymer matrix, and two functional fillers with a two-dimensional structure are selected; one is utilized to enhance the polarization performance and the other is employed to boost the breakdown strength. For the prerequisite of keeping the nanofiller space content unchanged, two kinds of gradient structures are designed to explore the effect of two-dimensional filler concentration gradient distribution on the breakdown, dielectric along with the energy storage performance of the composite dielectric. Finally, a discharge energy density of 19.22 J cm −3 along with a charge–discharge efficiency of 75% were obtained for the composite with both fillers in positive gradient distribution. The stochastic breakdown simulation results also verify the helpful contribution of the gradient structure to breakdown strength, which confirms the effectiveness of the gradient structure. This paper offers a brand-new structural design philosophy for the research and development of energy storage composite dielectrics that have high insulation and polarization.